Business model reinvention: Impacts of Covid-19 in the hospitality business - Adam, O.; Jerónimo, C.; Pereira, L.; Gonçalves, R.; Dias, Á.; Lopes da Costa, R. (Sustainability in software engineering and business information management. Lecture Notes in Information Systems and Organisation, 2023)
Currently, the hospitality business is facing severe challenges due to the COVID-19 pandemic, forcing hotels to quickly adapt to a new operational reality and address in a critical way the sustainability challenge. Such adaptation requires redefining the current business models since they are not adequate for the present global scenario. The study primary goal is to analyse the main impacts of COVID-19 in the hospitality business and propose a general reinvented business model, aiming to contribute to the hospitality industry’s reinvention in the global scenario. A literature review was developed to fulfil these objectives, and an in-depth interview was conducted with 14 professionals who work at different hotels. The obtained results demonstrated the reinvention of the hotels’ business model must include significant investment in technology and digital communication since these two are vital for the industry’s growth and evolution by providing customers with a sense of trust.